Two new species of the batfish genus Malthopsis (Lophiiformes: Ogcocephalidae) from the Western Indian Ocean - Ho, Hsuan-Ching (Zootaxa, 2013)
Two new species of the triangular batfishes, genus Malthopsis, are described from the western Indian Ocean. Both belong to a species group with minute prickles on the ventral surface. Malthopsis bradburyae n. sp. differs from its congeners by having the body covered by blunt, flat bucklers; subopercular buckler dull, without well-developed spines, its ventral surface covered by minute prickles and a few large bucklers anterior to the pelvic-fin base; rostrum moderately long, directed forward rather than upward; eye relatively small. Malthopsis austrafricana n. sp. differs from its congeners by having a long forward and horizontally directed rostrum; subopercular bucklers dull, without well-developed spines; ventral surface evenly covered by minute prickles and small bucklers; small black patches on dorsal surface; and a strong tail. Comments and a key to the Western Indian Ocean species of Malthopsis are provided.